Bibliometric Analysis of Social Studies Learning Models in Elementary Schools from 2014 to 2024 - Wibowo, Dimas Satrio; Muhroji, Muhroji (Journal Evaluation in Education (JEE), 2025)
Purpose of the study: This study aims to map and analyze publication trends related to Social Studies (IPS) learning models at the elementary school level using bibliometric data from the Scopus database covering the period 2014–2024.Methodology: This study employs a qualitative bibliometric method with four stages: Identification, Screening, Eligibility, and Inclusion. Data were retrieved from the Scopus database using the keywords TITLE-ABS-KEY(“social sciences”) AND TITLE-ABS-KEY(“learning model”) AND TITLE-ABS-KEY(“primary school”). Analysis tools used include Microsoft Excel and VOSviewer version 1.6.19.Main Findings: Publication trends fluctuate over the years with an increase in 2024. Scientific articles are the dominant document type (73.3%), and social sciences are the most frequently studied field (53.6%). Spain ranks first in publication and citation counts. Keyword co-occurrence analysis reveals “curriculum,” “education,” and “social sciences” as the most connected terms.Novelty/Originality of this study: This study provides the first bibliometric mapping of a global study on social studies learning models at the elementary level using Scopus data. This study advances new insights on understanding through publication trend patterns by identifying so as to support future policymaking, curriculum planning, and research direction in primary education. This study is used to recommend the development of social studies learning models that are relevant to 21st-century needs, such as the integration of digital literacy, collaboration, and project-based learning.